Cell technology and plasma therapy (PRP) in the restoration of hair follicles - Breurosh, Bohdan (Global Prosperity, 2025)
Abstract. The purpose of the work. To find out the mechanisms of action of PRP therapy and cell technologies in alopecia, to evaluate the changes in hair follicles at the biological level and to determine to what extent these methods contribute to hair growth. Materials and methods. Scientific publications on the use of platelet-rich plasma and stem cells in various forms of hair loss were analyzed. The effect of platelet growth factors on follicle cells, features of the immune response in alopecia areata, and the role of metabolic disorders in the deterioration of hair are considered. Results and discussion. Platelets contain bioactive components that activate regeneration: they increase the proliferation of follicle cells, improve microcirculation and reduce inflammation. Studies confirm changes in immune markers after a PRP course that correlate with hair regrowth. Stem cells show an even stronger effect, but the method is more complicated and expensive. The effectiveness of therapy differs between patients and depends on the type of alopecia, the state of metabolism and the work of the immune system. Hair loss has a negative effect on the psycho-emotional state, so the treatment is not only aesthetic, but also psychological. The best effect is provided by a comprehensive approach. Conclusions. PRP and cell technologies are promising methods affecting pathogenetic mechanisms of alopecia. However, further studies are needed to clarify optimal treatment regimens, identify groups of patients with the highest efficacy, and assess the duration of the obtained results.